2019
DOI: 10.1183/13993003.00118-2019
|View full text |Cite
|
Sign up to set email alerts
|

Failure with acquired resistance of an optimised bedaquiline-based treatment regimen for pulmonary Mycobacterium avium complex disease

Abstract: To the Editor: 5 years ago, a then 50-year-old woman presented with long-standing fatigue, dyspnoea and a chronic productive cough. Based on a computed tomography scan of the thorax and multiple positive cultures, she was diagnosed with nodular-bronchiectatic Mycobacterium avium pulmonary disease; she was also found to have a heterozygous F508del CFTR gene mutation. She commenced therapy with rifabutin 300 mg once daily, ethambutol 1200 mg once daily and azithromycin 500 mg once daily. After 15 months of ongoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…A study of bedaquiline as salvage therapy in 10 patients with refractory MAC or M. abscessus lung disease showed a clinical and microbiologic response in the majority of patients, although none achieved sustained culture conversion 67 . Subsequent studies have demonstrated the emergence of bedaquiline-resistant isolates 68, 69 , including seven of 16 bedaquiline-treated patients 69 . Bedaquiline may cause QT prolongation and other toxicity.…”
Section: Novel Treatmentsmentioning
confidence: 99%
“…A study of bedaquiline as salvage therapy in 10 patients with refractory MAC or M. abscessus lung disease showed a clinical and microbiologic response in the majority of patients, although none achieved sustained culture conversion 67 . Subsequent studies have demonstrated the emergence of bedaquiline-resistant isolates 68, 69 , including seven of 16 bedaquiline-treated patients 69 . Bedaquiline may cause QT prolongation and other toxicity.…”
Section: Novel Treatmentsmentioning
confidence: 99%
“…However, efficient responses to BDQ were observed in other animal models, such as zebrafish (12). Two studies reported poor or negative results for BDQ administration against nontuberculous mycobacteria-infected patients (27,28). However, recent studies showed that the activity of BDQ can be potentiated with adjunctive therapy, thus improving BDQ-based treatments (16,29).…”
mentioning
confidence: 99%
“…Emergence of resistance is a key problem in NTM treatment. Zweijpfenning et al have recently published a case where an increase in the bedaquiline MIC led to a resistant phenotype (or sub-population) of Mycobacterium avium complex resulting in failure of a bedaquilinebased treatment regimen [45]. We therefore believe that the combination with a highly active flourochinolon to efficiently suppress mycobacterial growth and the preceding intravenous induction therapy are key elements of successful treatment.…”
Section: Discussionmentioning
confidence: 95%